2021
DOI: 10.4103/eus-d-20-00252
|View full text |Cite
|
Sign up to set email alerts
|

Controversies in EUS: Do we need miniprobes?

Abstract: This is the fifth in a series of papers entitled “Controversies in EUS.” In the current paper, we deal with high-resolution catheter probes, otherwise known as EUS miniprobes (EUS-MPs). The application of miniprobes for early carcinomas in the entire intestinal tract, for subepithelial lesions, and for findings in the bile duct and pancreatic duct as well as endobronchial use is critically discussed. Submucous lesions, especially in the colon, but also early carcinomas in special cases are considered the most … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(8 citation statements)
references
References 255 publications
0
5
0
1
Order By: Relevance
“…In addition, in the guidelines for ESD and endoscopic mucosal resection for early gastric cancer, it is suggested that EUS may be useful as an additional diagnostic modality 3 . With the background of still unsatisfactory and complicated classification systems, EUS is still considered as an easy‐to‐use and complemental tool 20 . Further studies are needed to determine which type of lesion is necessary to undergo EUS examination before treatment.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, in the guidelines for ESD and endoscopic mucosal resection for early gastric cancer, it is suggested that EUS may be useful as an additional diagnostic modality 3 . With the background of still unsatisfactory and complicated classification systems, EUS is still considered as an easy‐to‐use and complemental tool 20 . Further studies are needed to determine which type of lesion is necessary to undergo EUS examination before treatment.…”
Section: Discussionmentioning
confidence: 99%
“…In 2021, a paper summarized the commercially available EUS-MPs and the multiple studies on their use on the gastrointestinal tract[ 22 ]. Hurlstone et al [ 23 ] reported the use of 12.5 MHz miniprobe ultrasonography for identifying cancer or broad-based polyps in the colon and rectum of 131 consecutive patients.…”
Section: Eus Examination Of Amnsmentioning
confidence: 99%
“…This technology is based on the premise that some diseases (such as cancer) cause changes in tissue hardness. 23 EUS-E is performed using conventional EUS probes, without additional instruments or real-time calculation of tissue distribution. The examination results are expressed in color superimposed on the traditional B-mode image, generally in blue for the hard tissue structure and in red for the soft tissue structure.…”
Section: Diagnostic Value Of Eus-derived Technologies For Colorectal ...mentioning
confidence: 99%